Substance misuse in elite athletes: Early detection, brief intervention, and referral to treatment - McDuff, D. R.; Garvin, M.; Chang, J.; Thompson, D. (Clinics in Sports Medicine, 2024)
Encounters with alcohol, cannabis, and nicotine/tobacco misuse is common.